Conversation Partnerships: An Educational Tool for Cross-Cultural Understanding - Kasten, Wendy C; Dagistan, Murat; Sarikaya, Vildan (Beyond Words, 2014)
This article describes one study of conversation partnerships between American students enrolled in teacher education programs, and international students enrolled at the same large midwestern university. Twenty-nine pairs of partners during one 15-week semester were directed to meet at least 10 times minimally 30 minutes each. Topics for initial meetings were recommended, to help partners get started. As the semester progressed, topics were based on interests and needs of the partners. Three data sources were collected and analyzed. International students were surveyed at the end of the program with demographic and open-ended question about their perceived outcomes of the experience. American students were required to keep and submit weekly logs of the meetings and their thoughts about the meeting. These students were further required to write an end-semester reflection paper, exploring their learning in areas of: better understanding the English language; learning about other cultures; and any other meaningful insights about the experience. These latter two data sources were analyzed qualitatively, using constant comparative analysis. Results of the study, overall, were positive with interesting insights from participants. International students reported improving their English. American students had their â€œeyes openedâ€ repeatedly about other cultures. Many of the partners reported the forming on genuine and hopefully sustainable friendships. Often, the partnerships went beyond the course requirements spending evenings, or weekend days together.